2020
DOI: 10.1002/mds.28015
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Cytokines and Neurodegeneration‐Associated Proteins in Parkinson's Disease

Abstract: Introduction Immune markers are altered in Parkinson's disease (PD), but relationships between cerebrospinal fluid (CSF) and plasma cytokines and associations with neurodegeneration‐associated proteins remain unclear. Methods CSF and plasma samples and demographic/clinical measures were obtained from 35 PD patients. CSF samples were analyzed for cytokines (together with plasma) and for α‐synuclein, amyloid β(1‐42) peptide, total tau, and phospho(Thr231)‐tau. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 18 publications
2
28
0
Order By: Relevance
“…PD often presents with an AD pathology such as senile plaques and neurofibrillary tangles (Apaydin et al, 2002), and several experimental studies have explained the co-pathology of AD and PD. α-synuclein has been shown to co-aggregate with amyloid-β 1-42 (Ono et al, 2012) and tau (Guo et al, 2013), and some of the studies in this review showed that CSF αsynuclein levels were correlated with those of amyloid-β 1-42 (Buddhala et al, 2015;Compta et al, 2015;Skogseth et al, 2015;Hall et al, 2016;Murakami et al, 2019;Wijeyekoon et al, 2020) and tau (Kang et al, 2013;Buddhala et al, 2015;Compta et al, 2015;Hall et al, 2015Hall et al, , 2016Skogseth et al, 2015;Murakami et al, 2019). These reports support an interaction of α-synuclein with amyloid beta and tau in the progressive course of PD and cognitive deterioration.…”
Section: Involvement Of Pathogenic Proteins Other Than α-Synucleinsupporting
confidence: 65%
See 1 more Smart Citation
“…PD often presents with an AD pathology such as senile plaques and neurofibrillary tangles (Apaydin et al, 2002), and several experimental studies have explained the co-pathology of AD and PD. α-synuclein has been shown to co-aggregate with amyloid-β 1-42 (Ono et al, 2012) and tau (Guo et al, 2013), and some of the studies in this review showed that CSF αsynuclein levels were correlated with those of amyloid-β 1-42 (Buddhala et al, 2015;Compta et al, 2015;Skogseth et al, 2015;Hall et al, 2016;Murakami et al, 2019;Wijeyekoon et al, 2020) and tau (Kang et al, 2013;Buddhala et al, 2015;Compta et al, 2015;Hall et al, 2015Hall et al, , 2016Skogseth et al, 2015;Murakami et al, 2019). These reports support an interaction of α-synuclein with amyloid beta and tau in the progressive course of PD and cognitive deterioration.…”
Section: Involvement Of Pathogenic Proteins Other Than α-Synucleinsupporting
confidence: 65%
“…In this cohort, CSF levels of α-synuclein correlated with those of amyloid-β 1-42 and total tau. Wijeyekoon et al (2020) showed that the CSF α-synuclein level was negatively correlated negatively with semantic fluency score and positively with the CSF level of amyloid-β 1-42 in PD.…”
Section: Results Showing That a Higher Csf α-Synuclein Level Indicates Worse Posterior Cognitive Functionmentioning
confidence: 97%
“…PD originates from the progressive loss of nigral dopaminergic (DAergic) neurons, which is accompanied by the accumulation of misfolded aggregated αSyn (αSyn agg ) within Lewy bodies and Lewy neurites which is a classical pathological hallmark of this disease (Dickson, 2012). Additionally, microglia-derived expression of pro-inflammatory cytokines such as IL-1β and TNF-α and the pro-oxidant NOS have been identified in the substantia nigra (SN), putamen, serum, and CSF of PD patients (Knott et al, 2000;Nagatsu et al, 2000;Frigerio et al, 2005;Teschke et al, 2014;Qin et al, 2016;Chen et al, 2018;Wijeyekoon et al, 2020). Numerous mechanisms have been implicated in PD pathogenesis, including mitochondrial dysfunction, endoplasmic reticulum stress (ERS), impaired proteostasis, and chronic neuroinflammation (Block et al, 2007) yet the exact mechanisms underlying increased vulnerability of nigral DAergic neurons to PD pathogenesis remains undefined.…”
Section: Introductionmentioning
confidence: 99%
“…First, the peripheral inflammatory condition may play a role in the CNS pathology, or at least reflect the course of it, and second, inflammation may be associated with and, perhaps, underlie non-motor symptoms of PD (Williams-Gray et al, 2016). A more recent study questioned whether peripheral immune changes causally contribute to the progression of PD, reporting that serum levels of cytokines do not correlate with CSF content, and suggesting that central and peripheral cytokine levels may partially behave independently, and may be driven by different factors (Wijeyekoon et al, 2020). Additional evidence of a chronic and systemic inflammatory state comes from studies showing the altered profile of immune cell composition in the blood of PD patients as compared to healthy individuals, reporting for instance, an increase in monocyte number and a decrease in the CD4+ T cell to CD8 cytotoxic T cell ratio (Bas et al, 2001;Grozdanov et al, 2014).…”
Section: Parkinson's Diseasementioning
confidence: 99%